2001
DOI: 10.1037/0022-3514.80.3.365
|View full text |Cite
|
Sign up to set email alerts
|

Chronic and temporary distinct expectancies as comparison standards: Automatic contrast in dispositional judgments.

Abstract: In 4 studies, the authors examined whether making outcome expectancies distinct resulted in their use as comparison standards and, consequently, in contrastive dispositional inferences for a target's behaviors. The expectancies examined were based on either chronic future-event expectancies (Study 1) or temporary, manipulated expectancy standards (Studies 2-4). Analyses revealed that when contextual expectancies were distinct or separable from target information, participants' dispositional judgments were cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…It seems entirely possible that our general instructions suggesting that both ability and task difficulty typically affect performance might not only have made participants' self-generated situational inferences salient but also might have activated proceduralized correction processes (Lucas, Krull, & Pelham, 1999;Weary, Tobin, & Reich, 1999). Heider's (1958) analysis of perceivers' intuitive theories of action suggested the operation of a compensatory schema (Kelley, 1972) for the effects of ability and environmental difficulty on performance outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It seems entirely possible that our general instructions suggesting that both ability and task difficulty typically affect performance might not only have made participants' self-generated situational inferences salient but also might have activated proceduralized correction processes (Lucas, Krull, & Pelham, 1999;Weary, Tobin, & Reich, 1999). Heider's (1958) analysis of perceivers' intuitive theories of action suggested the operation of a compensatory schema (Kelley, 1972) for the effects of ability and environmental difficulty on performance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few researchers recently have found evidence that, with sufficient motivation and cognitive resources, perceivers can effortfully correct their categorizations for biasing influences, at least under certain circumstances (Thompson, Roman, Moskowitz, Chaiken, & Bargh, 1994). For example, Weary et al (1999) recently have demonstrated that perceivers can recategorize behavior if they are aware of a biasing influence on their initial judgments and if they perceive that influence to be illegitimate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations